Pour une Histoire Culturelle des Cercles Hispaniques du XIXe siècle - Zozaya-Montes, Maria (2013)
Since the 1960´s, the study of nineteenth century associations have been analyzed with the focus of Social History, following Maurice Agulhon´s studies. Few historians study those associations on a Cultural way. My on-going research mixes historical analysis with antropological focus ("etic" and "emic" approach categories). Therefore, I propose a Cultural History to review sociability spaces, especially in the case I am focusing, Iberian Associations. Then, to explore the relevance of those clubs, great importance is given to the external images circulating about them, and the common identities created among and around them.